Comparative Analysis of Financial Performance Based on the PEARLS Method in Credit Unions under PUSKOPDIT Nusa Tenggara Timur - Lewar, Maria Viviana Nurak (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This research aims to compare the financial performance of Credit Unions under Puskopdit NTT based on the PEARLS method. The data used in this study are from 2016-2020, and a descriptive method was employed. The data analysis employs quantitative methods, specifically financial ratio analysis, using 13 PEARLS indicators applied by Credit Unions in accordance with standards set by the World Council of Credit Unions (WOCCU). The variables and measurements in this study comprise protection, effective financial structure, asset quality, revenue and expense acquisition rates, liquidity, and indicators of growth. The data collection methods used are documentation and interviews. Research results from 2016 to 2020 indicate that Credit Unions with excellent financial performance are Credit Union Pintu Air, Credit Union Obor Mas, Credit Union Sangosay, Credit Union Serviam, Credit Union Sinar Harapan, and Credit Union Tuke Jung. Credit Unions with financial performance in the good category are Credit Union Swasti Sari, Credit Union Ankara, and Credit Union Suka Damai. Meanwhile, the Credit Union with financial performance in the moderate category is Credit Union Mitan Gita.